A Review of Systematic Reviews on Pain Interventions in Hospitalized Infants. (2008) - Yamada, Janet; Stinson, Jennifer; Lamba, Jasmine; Dickson, Alison; McGrath, Patrick J; Stevens, Bonnie
Abstract : BACKGROUND: Hospitalized infants undergo multiple, repeated painful procedures. Despite continued efforts to prevent procedural pain and improve pain management, clinical guidelines and standards frequently do not reflect the highest quality evidence from systematic reviews. OBJECTIVE: To critically appraise all systematic reviews on the effectiveness of procedural pain interventions in hospitalized infants. METHODS: A structured review was conducted on published systematic reviews and meta-analyses of pharmacological and nonpharmacological interventions of acute procedural pain in hospitalized infants. Searches were completed in the Cochrane Database of Systematic Reviews, MEDLINE, EMBASE, CINAHL and PsycINFO. Two reviewers independently selected articles for review and rated the methodological quality of the included reviews using a validated seven-point quality assessment measure. Any discrepancies were resolved by a third reviewer. RESULTS: Of 1469 potential systematic reviews on interventions for painful procedures in hospitalized infants, 11 high-quality reviews were included in the analysis. Pharmacological interventions supported by research evidence included premedication for intubation, dorsal penile nerve block and EMLA (AstraZeneca Canada, Inc) for circumcision, and sucrose for single painful procedures. Non-nutritive sucking, swaddling, holding, touching, positioning, facilitative tucking, breast feeding and supplemental breast milk were nonpharmacological interventions supported for procedural pain. CONCLUSION: There is a growing number of high-quality reviews supporting procedural pain management in infants. Ongoing research of single, repeated and combined pharmacological and nonpharmacological interventions is required to provide the highest quality evidence to clinicians for decision-making on optimal pain management.